Sustainable and responsible investment dynamic cross-asset portfolio - Robiyanto Robiyanto; Andrian Dolfriandra Huruta; Budi Frensidy; Ashalia Fitri Yuliana (Cogent Business & Management, 2023)
Nowadays, the ESG-oriented portfolios are very popular. This study aims to study the performance of cross-asset portfolios between eco-friendly stocks (represented by Sri-Kehati index) with cryptocurrencies, bonds and gold. The data used in the study were the daily return of each instrument from January 2019 to December 2021, which was then analyzed using the DCC-GARCH analysis technique. The results show that adding Ripple, gold and bonds into a portfolio consisting of Sri-Kehati stocks can reduce the investment risk. The findings imply that investment managers and investors who have portfolios consisting of eco-friendly stocks such as Sri-Kehati stocks and bonds may reduce investment risk and balance their portfolios by adding gold or cryptocurrencies separately.
Keywords: G15; G11; Q59; 650; DCC-GARCH; dynamics portfolio; hedging effectiveness; optimal hedge ratio